NLRP3 Inflammasome Is Involved in Calcium-Sensing Receptor-Induced Aortic Remodeling in SHRs - Xin Zhang; Siting Hong; Shuhan Qi; Wenxiu Liu; Xiaohui Zhang; Zhiyu Shi; Wenjia Chen; Meng Zhao; Xinhua Yin (Mediators of Inflammation)
Increasing evidence suggests that the NLRP3 (nucleotide oligomerization domain-like receptor family, pyrin domain containing 3) inflammasome participates in cardiovascular diseases. However, its role and activation mechanism during hypertension remains unclear. In this study, we tested the role and mechanism of calcium-sensing receptor (CaSR) in NLRP3 inflammasome activation during hypertension. We observed that the expressions of CaSR and NLRP3 were increased in spontaneous hypertensive rats (SHRs) along with aortic fibrosis. In vascular smooth muscle cells (VSMCs), the activation of NLRP3 inflammasome associated with CaSR and collagen synthesis was induced by angiotensin II (Ang II). Furthermore, inhibition of CaSR and NLRP3 inflammasome attenuated proinflammatory cytokine release, suggesting that CaSR-mediated activation of the NLRP3 inflammasome may be a therapeutic target in aortic dysfunction and vascular inflammatory lesions.